Literasi Media Digital Pada Komunitas Pariwisata di Kawasan Danau Toba - Pratama, Yohanssen; Sinaga, Arnaldo Marulitua; Sianturi, Riyanthi Angrainy; Situmorang, Verawaty (Jurnal Master Pariwisata (JUMPA), 2021)
Lake Toba region is included in one of the 10 priority tourism destination locations. To answer the challenges of changing world tourism trends that utilize digital technology, several strategies must be carried out. In digitizing the process, it is necessary to involve the local community in formulating regulations, strengthening value chain partnerships between businesses in the tourism sector, increasing motivation and enabling the community through various kinds of assistance and training. Therefore, research is conducted that has the aim to develop the tourism potential of the Lake Toba Region through digitalization with the concept of community empowerment. As the output of this research, a community will be formed in each Lake Toba District, so that based on this community various development policies and strategies can be formulated in overcoming problems and developing the tourism sector in the Lake Toba region. Keywords: Community Based Tourism, Digitalization, Lake Toba, Local community, Literacy